1997
DOI: 10.1073/pnas.94.16.8462
|View full text |Cite
|
Sign up to set email alerts
|

MLN64 contains a domain with homology to the steroidogenic acute regulatory protein (StAR) that stimulates steroidogenesis

Abstract: MLN64 is a protein that is highly expressed in certain breast carcinomas. The C terminus of MLN64 shares significant homology with the steroidogenic acute regulatory protein (StAR), which plays a key role in steroid hormone biosynthesis by enhancing the intramitochondrial translocation of cholesterol to the cholesterol side-chain cleavage enzyme. We tested the ability of MLN64 to stimulate steroidogenesis by using COS-1 cells cotransfected with plasmids expressing the human cholesterol side-chain cleavage enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
154
2
4

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 223 publications
(172 citation statements)
references
References 18 publications
10
154
2
4
Order By: Relevance
“…The transport of cholesterol substrate for P450scc into mitochondria is performed by specific cholesterol transporting proteins, StAR or MLN64 (Bose et al, 2000;Stocco, 2000;Watari et al, 1997). Using specific antibodies that recognize a common epitope for both MLN64 and StAR (Bose et al, 2000), we detected the expected protein with MW of 55 kDa (Slominski et al, 2004c) corresponding to MLN64 (Uribe et al, 2003) in human and rodent skin samples.…”
Section: Cytochrome P450scc Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The transport of cholesterol substrate for P450scc into mitochondria is performed by specific cholesterol transporting proteins, StAR or MLN64 (Bose et al, 2000;Stocco, 2000;Watari et al, 1997). Using specific antibodies that recognize a common epitope for both MLN64 and StAR (Bose et al, 2000), we detected the expected protein with MW of 55 kDa (Slominski et al, 2004c) corresponding to MLN64 (Uribe et al, 2003) in human and rodent skin samples.…”
Section: Cytochrome P450scc Systemmentioning
confidence: 99%
“…Using specific antibodies that recognize a common epitope for both MLN64 and StAR (Bose et al, 2000), we detected the expected protein with MW of 55 kDa (Slominski et al, 2004c) corresponding to MLN64 (Uribe et al, 2003) in human and rodent skin samples. Additional immunoreactive proteins of lower MW (37 kDa and 18 kDa) could represent products of MLN64 processing and/or the full-length StAR protein (Bose et al, 2000;Stocco, 2000;Watari et al, 1997). This suggests that mammalian skin cells are biochemically equipped for cholesterol transport as the basis for steroidogenesis.…”
Section: Cytochrome P450scc Systemmentioning
confidence: 99%
“…The functional relation between MLN64 and StAR was previously addressed. It was shown that, like StAR, MLN64 can enhance steroidogenesis in vitro (Watari et al, 1997). Moreover, the region conserved between StAR and MLN64, the StAR-related transfer (START) domain was shown to be a cholesterol-binding domain for both proteins (Tsujishita and Hurley, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…MLN64 was originally discovered as a gene amplified in breast and ovarian cancers. It contains a C-terminal domain with 37% amino acid identity and 60% amino acid similarity to the C-terminal domain of StAR (13,14). The N terminus of MLN64 contains a leader sequence and four putative transmembrane domains, distinguishing it from StAR and suggesting that MLN64 functions in a different subcellular compartment.…”
mentioning
confidence: 99%
“…The N terminus of MLN64 contains a leader sequence and four putative transmembrane domains, distinguishing it from StAR and suggesting that MLN64 functions in a different subcellular compartment. The MLN64 START domain was subsequently found to have StAR-like activity in that it could promote steroidogenesis in a model cell system (14). Like the StAR START domain, the MLN64 START domain binds cholesterol, stimulates the movement of free cholesterol from sterol-rich donor vesicles to acceptor membranes, and augments steroid synthesis when added to isolated mitochondria (10,15).…”
mentioning
confidence: 99%